The determinants of private investment: Evidence from South Africa - Maluleke, Glenda (Economic Journal of Emerging Markets, 2024)
Purpose ─ This paper examines the determinants of private investment. The result can help the government determine which investment drivers to consider when formulating policies to stimulate private investment.Methods ─ It uses a Nonlinear Autoregressive Distributed Lag (NARDL) estimation approach with time series data from 1965 to 2022. Findings ─ The results indicate that positive shocks in economic growth lead to an increase in private investment over the long term. Conversely, both positive and negative shocks in inflation are found to positively impact private investment in the long run. Additionally, domestic credit to the private sector has a negative impact in both the short and long term. Implications ─ The government should develop policies designed to create an environment conducive to private investment. These policies should focus on ensuring easy access to finance, enhancing the openness of the economy, and maintaining a low and stable inflation rate.Originality ─ Few studies have fully explored the important drivers of private investment, especially in South Africa. Moreover, the studies conducted in South Africa have used other cointegration techniques, which are relatively weak compared to the NARDL used in the current study.